A review of power generation with thermoelectric system and its alternative with solar ponds. (January 2018) - Ding, L.C.; Akbarzadeh, A.; Tan, L.
Abstract: By using the Seebeck effect to produce electrical voltage, thermoelectric as a highly scalable, stationary and silent heat engine has undergone a state of vigorous research. Starting with the review on thermoelectric generators, it shows that thermoelectric is gaining more attention since the past decade. Generally, the research conducted on the thermoelectric generators concentrate on the material development, mathematical and numerical model development as well as the application of thermoelectric generators. For this article, attention is given to the application research of the thermoelectric generators. From the survey conducted, most of the application research carried out is based on intermittent electrical power generation (e.g. the direct use of solar energy available or waste heat recovery). Hence, it opens an opportunity for the research on the application of thermoelectric generators by utilising a heat source that is continuously ready for thermal-electrical energy conversion, such as phase change material, geothermal heat or solar pond. In the later section, the review is continued by introducing solar pond, a facility that has been used as a supply of low-grade heat source at the remote area or industrial process heating. The research on the fundamentals of solar pond and its applications, but not limited to, the power generation has also been summarised. The ultimate idea of this review is to provide an insight that a thermal-storage based heat source (e.g. in this review, the solar pond) could be useful for small-scale electric power generation, despite its ordinary function as low-grade heat source provider via heat extraction. Highlights: A review of the recent research of thermoelectric generators is presented. The research on the solar pond as a heat source is discussed. Power generation with thermoelectric generators and solar ponds is possible.